Data Collection Methods on Learning Outcome, Student Achievement and Academic Achievement - Lestari, Utami Puji; Setiawan, David Firna (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
Learning outcome, student achievement and academic achievement are some of the variables that get a lot of attention in educational research. Nevertheless, from several national studies collected there are inconsistencies in particular with regard to English terminology as well as inconsistencies in methods and instruments of data collection. Therefore, this study aims to explain the different methods of data collection research on learning outcome, achievement learning, and academic achievement. This study is a study desk study using literature review to explain the different methods of data collection on learning outcome, student achievement, and academic achievement. Based on the results of research can be concluded that the method of data collection of learning outcome, can be done through three ways, namely, perception survey, interview, and forum group discussion (FGD). While the instruments that can be used to collect data learning results are questionnaires, interview guides and minutes. Methods of collecting research data about student achievement, can be done through two ways namely, (1) test and (2) non test. Data collection methods of academic achievement can be done through documentation.